The mission and message of music : building blocks to the aesthetics of music in our time - Smoira-Cohn, Michal (Cambridge Scholars, 2010)
This book is an English re-writing of the original Hebrew edition, published by Dvir Publishing House, in 2007, and written jointly with the late Herzl Shmueli. The book probes into the nature and quality of the beauty and meaning of music. According to.